Pascal selective laser trabeculoplasty (PSLT) in the treatment of ocular hypertension and open-angle glaucoma compared to travoprost eye drops: A non-inferiority clinical trial - Rafaela C. M. C. de Almeida; Rodrigo L. Lindenmeyer; Fabio Lavinsky; Daniel Lavinsky; Egidio Picetti; Mônica O. da Silva; Diane R. Marinho; Thainá S. Moreira; Victória A. Silveira; Leonardo Leivas; Leonardo da C. Meireles; Helena M. Pakter (PLoS ONE, 2026)
Aims To compare the effectiveness of PSLT and the use of topical prostaglandin eye drops in the treatment of ocular hypertensive (OHT) or open-angle glaucoma patients (POAG) in reducing intraocular pressure (IOP) and peak IOP. Methods This is a non-inferiority randomized clinical trial, after washout, both patients eyes were randomized, one eye treated with PSLT (intervention group) and the contralateral eye treated with travoprost eye drops (controls). IOP, peak IOP by water drinking test (WDT), visual field (VF) and OCT were performed at baseline and at 7 days, 2, 6, 9 and 12 months after treatment. The primary outcome measure was to assess if the impact of PSLT on IOP and peak IOP is not inferior to that of the standard treatment (travoprost eye drops) by a margin not greater than the predefined threshold of 1.5 mmHg. Results A total of 30 patients participated in this trial. The mean baseline IOP was similar in both groups, 18.8 ± 4.0 mmHg and 18.8 ± 4.2 mmHg, intervention and control respectively. At 2, 6 and 9 months of treatment no significant difference in IOP was found between the two groups. At 12 months of follow-up the PSLT group showed lower average IOP (13.5 ± 2.3 mmHg versus 14.9 ± 2.7 and p < 0.001). Similar results were found for peak IOP in the WDT. On average there was no progression over time and no significant difference between groups regarding VF and OCT parameters. Conclusion PSLT was as effective as prostaglandin eye drops in reducing IOP and IOP peak in POAG and OHT patients. These findings are especially important as interest grows in minimally invasive glaucoma treatments and reducing reliance on topical medications. Trial registration Clinicaltrials.gov NCT05241938